INVESTIGATING COMPONENTS OF THE COMPETENCY - BASED CURRICULUM DEVELOPMENT USING PDSA AND SINGLE LOOP LEARNING CONCEPTS FOR STAND - ALONE SCHOOLS - Yangjeen, Somkiat; Vehachart, Rungchatchadaporn; Wannapairo, Suntaree (Journal of MCU Nakhondhat, 2023)
This article was to study the components and indicators of competency - based curriculum development using Plan - Do - Study - Act (PDSA) and Single Loop Learning concepts for stand alone schools under the Office of the Basic Education Commission (OBEC). The research was carried out using the mixed method research that combines and integrates qualitative and quantitative research methods, including studying and analyzing related documents and research, collecting data from schools that provide competency -based education, synthesizing components and indicators, and analyzing the components and indicators by a confirmatory factor analysis (CFA). It was found that there are 4 components with 25 indicators that are consistent with the empirical data with a Chi - square (χ2) of 559.36 at a degree of freedom (df) of 144, which can be calculated to a relative Chi - square of 2.31, a comparative fit index (CFI) of 0.99, a root mean square error of approximation (RMSEA) of 0.07, and a standardized root mean square residual (SRMR) of 0.04. The significance of the components can be ordered according to the completely standardized solution (CS) values as follows; ACT: Summary of the results and promulgate the competency - based school curriculum (CS = 0.99), DO: Prepare for developing curriculum and course structures (CS = 0.98), STUDY: Implement the draft competency - based school curriculum to teaching and learning (CS = 0.95), and PLAN: Set goals for developing a competency - based school curriculum (CS = 0.94), respectively. With all components and indicators taken into account, it can be concluded that school administrators should take a leading role in empowering teachers, school personnel, and communities to provide education that prepares students to face challenges in the future.